The Forms of Hate Speech in Twitter Comment Columns - Afria, Rengki; Fardinal, Fardinal; Fatrizal, Fatrizal; Maharja, Syafria (Jurusan Sejarah, Seni, dan Arkeologi, FKIP, Universitas Jambi, 2024)
Technological developments are not only in the form of positive impacts, but also have a negative impact, namely the emergence of various types of violations and even a crime, namely Hate Speech. This research is qualitative descriptive research. The purpose of this study is to: (1) describe the form of hate speech contained in reader comments on twitter and (2) describe the meaning of hate speech in the reader's comments. The source of this research data is the reader comments found on twitter. Based on the results of the study two conclusions can be drawn. First, the form of utterances of hatred contained in Twitter reader comments such as humiliation, defamation, defamation, unpleasant acts, provoking and inciting.